The Effect of Origin Region on The Essential Oil Profile of Kasturi Tobacco Leaves From Steam Distillation and Solvent Extraction - Suci Nur Jannah; Ika Oktavianawati; I Nyoman Adi Winata; Ratih Hidayah; Fatimah Yusro (Indonesian Chimica Letters, 2025)
Kasturi tobacco is a major domestic commodity from Jember that is well-valued by cigarette manufacturers for its intense aroma and unique flavor. When faced with government restrictions on cigarette production, the tobacco industry actively explores product diversification, and tobacco essential oil has emerged as a promising alternative. This study focuses on the utilization of Kasturi tobacco leaves from two different geographical locations in South Jember (Balung) and North Jember (Kalisat) to investigate how their location affects the essential oil profile. This study used two main extraction techniques, namely steam distillation and solvent extraction, to collect essential oils. The essential oils were analyzed based on their yield (based on dry weight) and chemical composition using GC-MS. The study showed that in North Kasturi leaves, increasing the steam distillation time resulted in a gradual increase in yield and chemical diversity. However, the steam distillation results for South Kasturi could not be used because the profile obtained was not representative. The difference in extraction methods shows significant results. Essential oil from North Kasturi produced through steam distillation (11 hours) has a lower yield and fewer compounds compared to the solvent extraction method. Solvent extraction results show that North Kasturi tobacco leaves produce a higher yield (5.2426%) compared to South Kasturi (4.0890%). Conversely, South Kasturi oil shows more chemical compound variation (29 compounds) compared to North Kasturi (24 compounds). The results prove that geographical origin affects the essential oil profile.